DETERMINANTS OF E-TAX FILING ADOPTION OF SMALL AND MEDIUM SCALE ENTERPRISES IN BAUCHI AND YOBE STATES, NIGERIA - Shettima, Mustapha; Abubakar, Abdulkadir; Baba, Bello Usman (Kashere Journal of Management Sciences, 2024)
Electronic tax filing (e-filing) is an electronic platform for taxpayers to file their taxes through online means straight to the tax authority. The main purpose of this study is to investigate the determinants of the intention of the taxpayers to adopt e-tax filing in Nigeria, based on the Technology Readiness Index theory. The study adopted a cross sectional survey design using a structured questionnaire with a population of 24,598 and a sample size of 379 using Krejcie and Morgan (1970) formula. Stratified sampling technique is adopted in order to eliminate biasness and the reliability of the instrument was tested using Cronbach’s alpha test. The unit of inquiry are the small-scale and medium sized enterprises (SMEs) owners and managers within Bauchi and Yobe State, Nigeria. The collected data was analysed with SPSS, version 34. The findings disclosed that technology readiness index (TRI) innovativeness has no direct effect with the intention to adopt e-tax filing. However, the result indicated that optimism, discomfort and insecurity are the statistically significant factors influencing the readiness of taxpayers to adopt e-tax in Bauchi and Yobe. The study recommends that SMEs operators and practitioners should prioritize inculcation of e-tax filing and other relevant technologically inclined procedure into the running of their business.